2008
DOI: 10.1016/j.ultrasmedbio.2007.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Brain Barrier Disruption Induced by Focused Ultrasound and Circulating Preformed Microbubbles Appears to Be Characterized by the Mechanical Index

Abstract: This work investigated the effect of ultrasonic frequency on the threshold for blood-brain barrier (BBB) disruption induced by ultrasound pulses combined with an ultrasound contrast agent. Experiments were performed in rabbits using ultrasound pulses at 2.04 MHz using sonications with peak pressure amplitudes ranging from 0.3 to 2.3 MPa. BBB disruption was evaluated using contrastenhanced magnetic resonance imaging. The threshold for BBB disruption was estimated using probit regression. Representative samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
200
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(213 citation statements)
references
References 27 publications
12
200
1
Order By: Relevance
“…Recent studies have shown that larger microbubbles (4-5 and 6-8 μm) have a lower PRP threshold for BBB disruption than smaller bubbles (1-2 μm) (9, 20) when using PLs greater than 66.7 μs. Also, previous work, which analyzed concentrations of 0.01 to 0.25 μL∕g, did not show any significant differences in drug delivery concentration (16), which was in good agreement with other studies that used similar parameters (15).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Recent studies have shown that larger microbubbles (4-5 and 6-8 μm) have a lower PRP threshold for BBB disruption than smaller bubbles (1-2 μm) (9, 20) when using PLs greater than 66.7 μs. Also, previous work, which analyzed concentrations of 0.01 to 0.25 μL∕g, did not show any significant differences in drug delivery concentration (16), which was in good agreement with other studies that used similar parameters (15).…”
Section: Discussionsupporting
confidence: 91%
“…A PRP threshold has been previously shown (2,14), and the present study also confirms it at short PLs. Second, previous work has demonstrated that lower center frequencies (e.g., 0.25 and 0.6 MHz) reduce the PRP threshold of BBB disruption (15,18). Third, effective BBB disruption requires a time interval where no ultrasound was emitted (i.e., intervals between pulses or bursts).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, FUS sonication could damage the brain tissue via FUS-induced edema, hemorrhage, ischemia, and apoptosis (10,18,19). To minimize brain damage, recent studies have focused on optimizing FUS parameters combined with intravascular preformed microbubbles to minimize sonication-induced hemorrhage (5,6,9,20,21). To ensure safe operation, the role of MRI becomes even more important; MRI not only aids FUS to localize the target region to gauge the BBB disruption but also provides simultaneous monitoring to detect incipient hemorrhage or neuronal dysfunction (18,22).…”
mentioning
confidence: 99%
“…Recently, focused ultrasound (FUS) combined with intravascular ultrasound contrast agent (UCA) has been shown to transiently increase the transport of molecules across the BBB (4)(5)(6)(7). This increase in BBB permeability can be detected by contrast-enhanced MRI using gadolinium-based (8,9) or iron oxide-based contrast agents (10) or by single-photon emission computed tomography with 99m Tc-based radiotracers (11). Using these imaging methods to guide FUS sonication, BBB at the targeted brain regions can be disrupted accurately, facilitating the delivery of diagnostic or therapeutic agents (12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%